Designing the Future Of Work: Generational Shifts, Technology Integration, And Inclusive Practices - Hendratmoko, Suseno (Jurnal Manajemen Teknologi, 2025)
Abstract. This scholarly work offers an in-depth examination of the emerging challenges and opportunities that both employers and employees must consider to effectively adapt and thrive in the ever-evolving world. Purposeng was used to recruit interview and focus group participants based on their professional expertise and diverse demographic backgrounds. Stratified random sampling was also applied to ensure a balanced demographic representation. Content categorization was conducted on interview and focus group transcripts to identify recurring themes, patterns, and key insights. The findings confirm that the current work landscape is undergoing a dynamic transformation, particularly with the increased adoption of remote and hybrid work models. This shift is compelling organizations to reassess the design of physical workspaces, management systems, and internal communication structures. The rapid advancement of technology further necessitates a culture of continuous learning and adaptive thinking. Moreover, the integration of digital tools, automation, and data-driven decision-making is reshaping organizational cultures and structures to become more flexible and sustainability-oriented, reflecting the value shifts of the current and incoming workforce. Keywords: Future workplace, evolution of work, work environments